FUNCTIONAL BASIS OF READING IN PRESCHOOL CHILDREN 4-5 YEARS OLD WITH GENERAL SPEECH UNDERDEVELOPMENT - Turdalieva Shakhlo Khusnutdinovna (Journals Park Publishing, 2024)
The publication is devoted to the problem of early learning to read for children with speech impairments. The positive influence of early reading on the formation of a functional basis for reading in preschoolers with general speech underdevelopment is considered. The article discusses new approaches to early teaching of reading to preschoolers with speech impairments. The influence of teaching basic reading skills on the state of the functional foundations of reading in preschoolers 4-5 years old with general underdevelopment of speech is analyzed.
Keywords: functional basis of reading, neuropsychology, neuropsychophysiology, phonetics-phonemics, praxis, general underdevelopment, techniques.